A mutation associated with stress resistance in mice is associated with human grip strength and mortality. (3rd July 2019) - Newell-Stamper, Breanne L.; Huibregtse, Brooke M.; Boardman, Jason D.; Domingue, Benjamin W.
ABSTRACT: Hand grip strength (GS) is a valid and reliable predictor of future morbidity and mortality and is considered a useful indicator of aging. In this paper, we use results from the genetic analysis in animal studies to evaluate associations for GS, frailty, and subsequent mortality among humans. Specifically, we use data from the Health and Retirement Survey (HRS) to investigate the association between three polymorphisms in a candidate frailty gene ( Tiam1) and GS. Results suggest that the A allele in rs724561 significantly reduces GS among older adults in the US (b = −0.340; p < .006) and is significantly associated with self-reported weakness (b = 0.221; p = .036). This same polymorphism was weakly associated (one-tailed) with an increased risk of mortality (b = 1.091; p < .093) and adjustments for GS rendered this association statistically non-significant (b = 1.048; p < .361). Overall, our results provide tentative evidence that the Tiam1 gene may be associated with frailty development, but we encourage further studies.